2023
DOI: 10.1098/rsos.230080
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin supplementation ofDrosophila melanogasterlarvae results in less viable adults with smaller cells

Abstract: The intrinsic sources of mortality relate to the ability to meet the metabolic demands of tissue maintenance and repair, ultimately shaping ageing patterns. Anti-ageing mechanisms compete for resources with other functions, including those involved in maintaining functional plasma membranes. Consequently, organisms with smaller cells and more plasma membranes should devote more resources to membrane maintenance, leading to accelerated intrinsic mortality and ageing. To investigate this unexplored trade-off, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…For example, at high temperatures, small-celled fish species were found to tolerate hypoxia better than large-celled species [27]. In other studies, small-celled forms of adult D. melanogaster were induced developmentally by larval feeding with rapamycin, a drug that downregulates the activity of the TOR kinase in TOR complex 1, reducing downstream signalling coming from this part of the TOR/insulin pathways [63,64]. The small-celled flies in these studies showed better flight performance under hypoxia than large-celled flies, and this effect was temperature-dependent [26], but they suffered increased mortality during early adulthood [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, at high temperatures, small-celled fish species were found to tolerate hypoxia better than large-celled species [27]. In other studies, small-celled forms of adult D. melanogaster were induced developmentally by larval feeding with rapamycin, a drug that downregulates the activity of the TOR kinase in TOR complex 1, reducing downstream signalling coming from this part of the TOR/insulin pathways [63,64]. The small-celled flies in these studies showed better flight performance under hypoxia than large-celled flies, and this effect was temperature-dependent [26], but they suffered increased mortality during early adulthood [63].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, small-celled forms of adult D. melanogaster were induced developmentally by larval feeding with rapamycin, a drug that downregulates the activity of the TOR kinase in TOR complex 1, reducing downstream signalling coming from this part of the TOR/insulin pathways [63,64]. The small-celled flies in these studies showed better flight performance under hypoxia than large-celled flies, and this effect was temperature-dependent [26], but they suffered increased mortality during early adulthood [63]. Our results here suggest that the effects of variation in cell size between flies may also partially account for changes in heat tolerance when flies are engaged in metabolically demanding activities, such as flight and climbing.…”
Section: Discussionmentioning
confidence: 99%